Sistema regional de inova????o da ovinocultura do Mato Grosso do Sul associado ao desenvolvimento da ovelha da ra??a pantaneira - Gomes, Narciso Bastos (2014)
This study presents a proposal of a regional model of innovation system idealized for sheep industry from Mato Grosso do Sul (MS) state ??? Brazil ??? bonded to the breendig of pantaneira sheep. Public and private agents, universities, financial institution and R&D centers composes such innovation system, which is committed through the innovation with the development of a nation, region or economy sector. According to the Schumpeter approach, the economic development is only possible under the effort of entrepreneurs, either by a set of agents committed with the creation of new products, processes and technologies or by their ability of disseminating them, which results in both technical and economic development. From Schumpeter approach and the Evolutionary Theory of Technological Development there has been a great advance on the recognition of the innovation system as a structure needed to revolutionize and develop nations, regions or sector. From the original idea of Schumpeter in pointing out the innovation as a driving force for the economic development and the innovation system as a strategy to develop learning and technologies through innovation, there has been a current evolution by some prospective studies focusing on the ???design??? and by the proposition of innovation system models of countries, regions and sectors. Thus, this study presents the regional innovation system as a strategy for the development of the pantaneira sheep industry productive chain in the state of MS. Since 2005, this activity has attracted the attention of public and private agents comprised with the breeding and slaughter, commerce, improvement of the animals as well as development and adaptation of such breed to the regional environment. Even in the 8thnational position in sheep flock and the 2nd regional position, MS state does not stand out as a great consumer nor as producer of meat, wool and other sheep sub-products. Aiming the standard breed, the regional agents of development has turned their attention to the pantaneira breed, by adopting some techniques of breeding, fattening, management, power and mortality reduction. This manuscriptis featured as single case study according to Yin perspective, with a qualitative and exploratory nature. The interview performed with eleven innovation agents chosen by snowball technique furnished the information that were analyzed via Content Analysis under Bardin (2009) perspective. We concluded that currently there is in the state the basis for the structuration of a engaged for the modernization of this regional activity through the strategies regional innovation system whose agents are the own actors that compose the sheep productive chain, who have been of professionalization and innovation under the neo-Schumpeter approach.